The Representation of Turkish Women in James Bond Films - Bayraktaroglu, Kerem (The journal of religion and film, 2019)
While there is ample academic material exploring the cinematic role of James Bond and the "Bond Girl", this paper chooses to focus on and examine the significance of Turkish female representations in three films set in Istanbul: From Russia with Love (Terence Young, 1963),The World Is Not Enough (Michael Apted, 1999) and Skyfall (Sam Mendes, 2012). The varying representations in these films are scrutinized to investigate how they distinguish Turkish female characters and the connotations of Istanbul over time and whether this depiction is connected with Turkey’s changing position vis-à-vis the Western world. These questions thus have historical implications and point to the country’s geopolitical role at the time each film was released, and its effects on the female’s depiction and the plot. From a contextual analytical standpoint, factors such as costume theory, sexual objectification, post-colonialism and the "male gaze" are taken into account in the examination of the case studies.